(untitled) (Ocean and Coastal Research, 2024)
This study evaluated the bioavailability of polycyclic aromatic hydrocarbons (PAHs) in Santos Bay (SB) and theadjacent Santos Continental Shelf (SCS) in Brazil. Biliary metabolites were measured in several fish species toestablish a baseline for future monitoring programs. Bile samples from different species of fish were collected monthlyfrom July to December 2005 in SB, and in August 2005 and February 2006 on SCS. Metabolite concentrationswere determined using high-performance liquid chromatography with fluorescence detectors. Naphthalene,phenanthrene, and benzo[a]pyrene metabolite concentrations ranged from 24 to 810 µg g-1 of bile, 1.8 to 68 µg g-1of bile, and below the limit of quantitation to 1.3 µg g-1 of bile, respectively. Despite its high concentrations, the levelsof naphthalene metabolites were in regions of low-contamination, while benzo[a]pyrene metabolite were in thesame range as those reported in moderately contaminated areas, which may indicate pyrolytic contaminationby PAHs. No significant differences in the metabolite concentrations were found between the SB and the SCSsamples or during the periods of collection. Future studies with a single biomonitoring species should be conducted,considering age, sex, and feeding condition of the individuals. The metabolite data presented in this study is animportant baseline information for this urbanized region, which hosts several sources of contaminants.